The challenges of aviation communication: Aspects of using aviation English - Rankov Dragana; Jovanović Tomislav; Kapor Nenad (Megatrend Revija)
In this paper, we deal with certain elements of aviation communication in civil aviation. The term "communication" usually includes all aspects of information transfer. It is an essential part of teamwork, and clarity of language, namely aviation English, takes a central place in the communication process. Different types of communication, especially verbal communication, remain one of the weakest links in the modern aviation system - this is the opinion of many researchers of this phenomenon. On the other hand, adequate communication requires that the recipient receives appropriate information, understands it and, based on it, can act appropriately. Communication is part of the technological process of providing air transportation services in a safe manner. This paper consists of parts of an unpublished paper by D. Rankov in 2024. - "The influence of the quality of interpersonal communication of executive staff on the air transportation safety".